High Hole Mobility in Long‐Range Ordered 2D Lead Sulfide Nanocrystal Monolayer Films. (23rd May 2016) - Zhao, Man; Yang, Fangxu; Liang, Chao; Wang, Dawei; Ding, Defang; Lv, Jiawei; Zhang, Jianqi; Hu, Wenping; Lu, Chenguang; Tang, Zhiyong
Abstract : Coupling between colloidal semiconductor nanocrystals (NCs) with long‐range order is critical for designing advanced nanostructures with controlled energy flow and charge carrier transport. Herein, under the premise of keeping long‐range order in 2D NC monolayer, its native organic ligands are exchanged with halogen ions in situ at the liquid–air interface to enhance the coupling between NCs. Further treatments on the films with dimethyl sulfoxide, methanol, or their mixture effectively improve carrier mobility of the devices. The devices show repeatable enhanced p‐type transport behavior with hole mobility of up to 0.224 ± 0.069 cm 2 V −1 s −1, the highest value reported for lead sulfide NC solids without annealing treatment. Thanks to accurate control over the surface of NCs as well as the structure of NC film, the ordered NC monolayer film of high hole mobility suggests great potentials for making reliable high performance devices. Abstract : Long‐range ordered monolayer thin films of lead sulfide (PbS) nanocrystals (NCs) are obtained by in situ exchanging native oleic acid ligands with halogen ions at the liquid–air interface. Further treatments on these films with dimethyl sulfoxide, methanol, or their mixture greatly enhance the coupling between NCs. The films exhibit good p‐type transport property from field effect transistors measurement with high hole mobility of 0.224 cm 2 V −1 s −1, representing the best thin film devices from PbS NCs.